Cassava starch, used as a substitute for aluminum sulfate, is effective in the primary treatment of cloudy water (Agroindustrial Science, 2020)
The objective of the present work was to evaluate the effectiveness of cassava starch in the primary treatment of residual waters. The study was carried out using the jar test technique by adding different doses of cassava starch at 1, 2 and 3% concentration. the different doses were compared with the optimal primary treatment of aluminum sulfate at a concentration of 1% that allows a 99.20% decrease in turbidity, 79,92% of total dissolved solids, 100% color and pH. Although pH levels decreased, they were kept within the maximum permissible limit of (6.5 - 8.5) pH. According to the tests carried out, the water treated with cassava starch is an alternative for the primary treatment of the water of the Shanusi River, since it allows us to comply with the requirements established in the sanitary standards of drinking water quality with regard to color and turbidity.